PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN MENULIS PARAGRAF ARGUMENTASI SISWA SMA - Yuniarti, Anna; Sulissusiawan, Ahadi; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to improve the quality of learning and to know the ability of student writing argumentative paragraph with the application of problem based learning model in teaching writing of argumentative paragraph. The subject of this research were 39 students in tenth grade students of SMA Negeri 10 Pontianak.  There were three cycles implemented in this research. The source of the data was from the tenth grade Bahasa Indonesia teacher through the lesson plan, the list of students 'attitudes score, the list of students' ability in writing argumentative paragraphs, and teacher activity used indirect techniques, that were observation and documentation. Based on the results of this research, it can conclude that the problem-based learning model improved the quality of the teaching learning process, especially the students' attitude and the students' ability in writing argumentative paragraphs. It can be proven from the precentage of students' attitudes and students' argumentative paragraph writing ability was increase from first cycle until third cycle. The students' attitudes tothe aspects of learning motivation, diligence, cooperation, discipline, and responsibility was increased from I cycles, II, and III. The mean score for I cycle of students' writing argumentative paragraphs was 56.15 and 33.33 % for learning mastery level. The Cycle II was increased to 73.08 and the learning mastery level was 56.41%. Cycle III there was a significant improvement, that was 79,74 and the learning mastery level was 79,49%. Keywords:   Problem Based Learning Model, Argumentative Paragraph, Classroom Action Research